Investigation on Copper Extraction Using Numerical Simulation - Marjani, Azam; Shirazian, Saeed (Asian Journal of Chemistry, 2011)
Extraction of Cu2+ with a kerosene solution of di(2-ethylhexyl)phosphoric acid (D2EHPA) in membrane contactors was studied in this work. Simulations were performed using computational fluid dynamics (CFD) of mass and momentum transfer in all subdomains of a circular membrane contactor. Conservation equations were derived and solved for Cu2+ in the membrane contactor. With solving conservation equations, concentration and pressure distributions were obtained for solute. Simulation results showed an extraction efficiency of 85.8 % for Cu2+.